Alzheimer's disease: characteristics and guidelines in dentistry - Alexandre Franco Miranda; Érica Negrini Lia; Soraya Coelho Leal; Maria da Penha Araújo Franco Miranda (Faculdade São Leopoldo Mandic, 2010)
Dementia is classified as a mental disorder of a neurodegenerative nature that affects the Central Nervous System. Alzheimer's disease is the most prevalent form of dementia that affects elderly people and it is defined as a progressive and persistent loss of multiple areas of intellectual functions. It gradually promotes deterioration in memory, learning, orientation, emotional stability and ability to communicate. Moreover, abstract thinking (paranoia and hallucinations) and the decline of personal care such as bathing and performing oral hygiene are common, interfering in the individual's social and daily life. According to its development, Alzheimer's disease is divided into three distinct stages: initial, intermediate and terminal stage. The aim of this study was to approach the characteristics and suggest guidelines for dental attendance in the representative stages in the development of this dementia condition. The dentist should be aware of the different stages of this disease and its characteristics to provide patients with individual oral health attention. The participation of caregivers, family, and the health team is fundamental and it is also necessary to maintain oral health of these elderly patients.